Characterisation of the bioactive properties and microstructure of chickpea protein-based oil in water emulsions. (July 2019) - Felix, Manuel; Cermeño, Maria; Romero, Alberto; FitzGerald, Richard J.
Abstract: Legumes, such as chickpea, represent a good source of high quality proteins for which there is an increasing global consumer demand. A chickpea protein concentrate (CP) was generated by isoelectric precipitation. Protein determination, electrophoretic and gel permeation chromatographic analysis revealed that the order of CP solubility was pH 7.5 > 2.5 > 5.0. Sunflower oil in water (O/W) emulsions were generated with the CP at pH 2.5, 5.0 and 7.5. Microstructural evaluation of the emulsions using laser light-scattering particle size analysis, optical microscopy and rheological analysis showed that smaller droplet size (3.1 ± 0.2 and 1.1 ± 0.1 μm) and the highest elastic moduli (876.0 ± 3.2 and 563.5 ± 6.5 Pa) were obtained in those emulsions generated with CP at pH 2.5 and 7.5. The ferric reducing (FRAP) and oxygen radical absorbance capacity (ORAC) values of the CP emulsions ranged from 194.5 ± 19.2 to 242.4 ± 8.4 μmol Trolox Eq·g −1 CP for FRAP at pH 2.5 and 5.0, respectively, and from 313.2 ± 2.6 to 369.0 ± 1.6 μmol Trolox eq·g −1 CP for ORAC at pH 5.0 and 2.5, respectively. The enzyme inhibitory activity of the emulsions was generally low irrespective of the pH value (c.a. 3 and 30% inhibition for dipeptidyl peptidase IV (DPP-IV) and angiotensin converting enzyme (ACE) activity, respectively). Simulated gastrointestinal digestion (SGID) of the emulsions significantly decreased their FRAP whereas it increased their ORAC values as well as their ACE and DPP-IV inhibitory activities irrespective of the pH value of the CP. These results demonstrate the potential application of reduced fat CP-stabilized emulsions for the provision of antioxidant and enzyme inhibitory activities. Graphical abstract: Unlabelled Image Highlights: The stability of chickpea-based emulsions was pH dependent. Smaller particle sizes and higher viscoelastic moduli were obtained at pH 2.5 and 7.5. The emulsions exhibited good in vitro bioactive properties. Simulated gastrointestinal digestion enhanced emulsion bioactivity.